Modifikasi Model Bauran Pemasaran Plus Terhadap Variabel Pembentuk Yang Positif Dan Signifikan - Minto Waluyo (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
PT. X Surabaya is a bookstore outlet that sell the book as its main business, for that company needs to make improvements and development to face the competition, to increase customer satisfaction and ultimately become loyal consumers. Variable proposed model starts from the marketing mix which is formed from the variables (product, price, youth get the product, distribution, promotion, location, diversity of products sold and services), corporate policies, consumer behavior, purchase decision, thus increasing the impact of consumer satisfaction loyal to the PT. X. The results show that modification of Marketing Mix Plus had a direct impact, positive and significant impact on its constituent variables namely Products of 0.482, Marketing Mix Plus had a direct impact, positive and significant impact on the price of its constituent variables of 0.343, Marketing Mix had Plus a direct impact, positive and significant impact on the distribution of its constituent variables 0.48, Marketing Mix Plus had a direct impact, positive and significant impact on its constituent variables namely Promotion of 0.641, Marketing Mix Plus had a direct impact, positive and significant impact on the location of its constituent variables of 0.443.